Genetic diversity and relatedness analysis of nine wild species of tree peony based on simple sequence repeats markers - Yuqian Xue (KeAi Communications Co., Ltd., 2021)
Tree peony has nine wild species, but the evolutionary relationship of them is still unclear. Here, a total of 274 specimens from 22 natural populations of nine wild species were collected, and their genetic diversity and similarity was analyzed based on Simple Sequence Repeats (SSR) molecular markers. A total of 106 alleles were generated based on 20 primers and with an average of 5.3 alleles per primer. Shannon's information index (I) ranged from 0.6333 to 1.7842, and the average of Nei's genetic diversity coefficient (H) was 0.5771. Polymorphism Information Content (PIC) value varied from 0.29 to 0.77, ten of these primers had high polymorphism (PIC ≥ 0.50). All the above genetic parameters of primers reflect more rich genetic diversity information compared with other researches using SSR molecular markers to study the genetic diversity of tree peony wild species. At the population level, the lowest and highest degree of genetic diversity occurred in Paeonia ludlowii-P1 and P. delavayi-P3 population, respectively. Whereas at species level, the genetic diversity of 9 wild peony species was as follows: P. lutea > P. delavayi > P. rockii > P. qiui > P. ostii > P. decomposita > P. potaninii > P. spontanea > P. ludlowii. Furthermore, cluster analysis at species level divided the nine wild tree peony species into two branches. In branch I, the closest phylogenetic relationship was found between P. ostii and P. rockii, followed by P. spontanea, P. qiui, and P. decomposita. In branch II, the closest relationship occurred between P. lutea and P. delavayi, followed by P. potaninii and P. ludlowii. Clustering results supported the division of tree peonies into two subsects (Delavayanae and Vaginatae), it also supported P. potaninii and P. ludlowii as independent species. The results provided novel insight into the genetic diversity and phylogenetic relationship of nine wild tree peony species. It will help formulate comprehensive protection measures of wild germplasm resources and select proper parents for distant hybridization in the future.